Measuring Human Balance on an Instrumented Dynamic Platform: A Postural Sway Analysis - Gouwanda, D.; Gopalai, Alpha Agape; Lim, Z.S.; Lim, King Hann (Springer link, 2013)
A system to monitor the trajectory and distribution of Center of Pressure (CoP) oscillations in real-time was designed. The system used a custom built force plate that measured sway area and sway velocity based on the measured CoP. A stable posture is reflected by a controlled CoP oscillation, where the oscillation lies within the limits of stability. Large magnitudes of CoP oscillations (large sway area) indicate weak proprioception strength and a heightened risk of falls. Experiments carried out involved self-induced perturbations that destabilized postural control among volunteers with active and inactive lifestyles. The observed results from the experiment indicate that individuals with active lifestyle have better postural control than individuals with inactive lifestyle. Subjectswith active lifestyles demonstrated greater sway velocities, while maintaining a small sway area.